THE EFFECTIVENESS OF MOBILISATION BY ADDING D5% FOR POST OPERATION PATIENT OF INTESTINES PERISTALTIC IN THE I.C.U ROOM - Emyk Windartik; Ima Rahma wati; Eka Nur So’emah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
The surgeon is a medical treatment using the invasive technique, ended by needling and closing of the wound assisted with anesthesia. The most primary grievance often occurs for the post-surgical operation are a body weakness, lack of muscle strength, query, vomit, a decreasing of nutrient and the duration of hospitalizing for the patient after surgical oper-action affected by an abdomen surgical. The intestine possibility manipulation during an operation involving immobility and lack of orally.those can affect the intestine function cause of various grievances. The purpose of this research was to discover and the concept of view deeply. Due on ambulation experience early at Islamic Hospital Sakinah, Mojokerto for post-surgical operation appendectomy. The research design used question experiment design, nonequivalent control group design. The population of this research was for all patients of post appendix surgical using anesthesia SAB through surgical at Sakinah Islamic hospital, Mojokerto in totally 43 respondents. The sample of this research was inference population by having selected for post operation in specific criteria of 30 people consist of15 conducting person group and 15 in controlling group. The independent variable of this research is a mobilization variable, and the dependent variable is an intestine peristaltic.The result of a paired t-test of mobilization impact shows an interesting data point p=0.000, And a=0.05 thus p<a means that the given Ho mobilization effected for intestine peristaltic therefor, the final result showed there was a mobilization causing of intestine peristaltic for appendectomy surgical operation at RSI Sakinah, Mojokerto. A given D5% mobilization is more effective in increasing for intestine peristaltic than non giving mobilization.